ANALYSIS OF BORROWINGS FROM THE FILM “I FINE.. THANK YOU.. LOVE YOU” - Udovichenko, Hannah; Ostapenko, Svitlana (SWorld-Ger Conference proceedings, 2024)
The paper deals with the issue of borrowing from both theoretical and practical perspectives. The authors analyze the reasons and preconditions for borrowing, its main types and signs of assimilation. The practical part of the work reveals two main types